1917 Cal. Stat. 221, ch. 145, § 1 - (:unkn) unknown (General Publisher, 1917)
Prohibited the manufacture, leasing, keeping for sale, offering, giving, or disposing of any instrument or weapon of the kind commonly known as a blackjack, slungshot, billy, sandclub, sandbag, bludgeon, metal knuckles, dirk, or dagger.
--
Keywords: TRANSFER; MANUFACTURE & POSSESSION - NON-GUN ARMS